PENGARUH PENERAPAN METODE PEMBELAJARAN MNEMONIK BERBASIS MEDIA MINI BOOK TERHADAP KEMAMPUAN DAYA INGAT PESERTA DIDIK PADA MATA PELAJARAN IPS DI KELAS VIII SMP RAUDLATUL MUTA’ALLIMIN - Lathifatus Suniyyah; Asnimawati Asnimawati; Ali Imron; Nurul Hasanah (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
Memory retention is a crucial aspect of Social Studies (IPS) learning, particularly regarding historical material that encompasses numerous facts, figures, and interconnected sequences of events. Preliminary observations in a Grade VIII class at SMP Raudlatul Muta'allimin revealed that only 28.9% of students achieved scores above the Minimum Mastery Criteria (KKM); students tended to memorize material by rote without employing meaningful encoding strategies. This study aimed to analyze the impact of a mnemonic learning method utilizing "mini-book" media on students' memory retention in Social Studies. A quantitative approach was employed using a Non-equivalent Control Group Design and purposive sampling, involving an experimental class (n=24) and a control class (n=26). Data were collected via pre-tests and post-tests and analyzed using normality, homogeneity, paired-sample t-tests, and independent-sample t-tests. The results indicate that the mnemonic learning method using mini-book media had a significant effect on students' memory retention, as evidenced by the paired-sample t-test (t-value 22.021; sig. 0.000 < 0.05) and independent-sample t-test (t-value 3.964; sig. 0.000 < 0.05). The experimental class demonstrated greater improvement than the control class, shifting from a predominance of low-to-medium category scores to 92% falling within the high category. Regarding specific indicators, encoding performance rose from 57% to 83%, and retrieval performance increased from 55% to 92%. Consequently, the mnemonic learning method using mini-book media serves as a viable alternative strategy for Social Studies instruction to enhance students' memory retention, especially for information-dense topics such as history.